2017
DOI: 10.1080/10962247.2017.1359701
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of mesitylene via mesoporous adsorbents

Abstract: This study aims to improve the performance of adsorbent for mesitylene, which is typically applied in the spray-coating industry. The zeolite MCM-41-AS is selected as a candidate for the investigation. Experimental results reveal that MCM-41-AS exhibits a good adsorption capacity for mesitylene and that it can be integrated with H-ZSM-5-25 for the simultaneous adsorption of mesitylene and toluene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Zeolite is widely used as chemical sieve, adsorbent and catalyst due to its excellent properties such as hydrophobicity, large surface area (250-800 m 2 g -1 ), tunable porosities, nonflammability. Specially, the textural properties of zeolite can be tailored by varying the Si/Al ratio (Nien et al, 2017). Carbon-based materials often suffer from the drawbacks of flammability and regeneration difficulty.…”
Section: Oxygen-contained Materials 221 Zeolitementioning
confidence: 99%
“…Zeolite is widely used as chemical sieve, adsorbent and catalyst due to its excellent properties such as hydrophobicity, large surface area (250-800 m 2 g -1 ), tunable porosities, nonflammability. Specially, the textural properties of zeolite can be tailored by varying the Si/Al ratio (Nien et al, 2017). Carbon-based materials often suffer from the drawbacks of flammability and regeneration difficulty.…”
Section: Oxygen-contained Materials 221 Zeolitementioning
confidence: 99%
“…Moreover, MCM-41 and its modified products exhibited a broad-spectrum capacity to adsorb many types of adsorbates, such as metal ions, dyes, gases, and drugs [16][17][18][19]. In addition, as-synthesized and modified MCM-41 exhibited good adsorption performance for organic compounds, particularly aromatic compounds such as benzene [20], mesitylene [21], phenol [22], toluene [23], aniline [24], and chlorophenol [25]. However, the chemical modification of MCM-41, which included amino, sulfhydryl, and metal modification, greatly increased synthesis costs due to the use of expensive reagents and complex modification methods, which limited the application of MCM-41 [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For the adsorption on zeolites, the acidic sites seemed to be a decisive factor in the affinity of a certain VOC (e.g., mesitylene) on the adsorbent surface. 39 Therefore, the NH 3 -TPD curves for H-ZSM-5 were collected and are shown in Figure 2c. It was found that the surface acidic amount of H-ZSM-5 decreased with the increase of SARs.…”
Section: Resultsmentioning
confidence: 99%